Best-first search as the simplification of weighted process algebra extension - Arellano, Rene C. (Animo Repository, 1994)
In the course of searching for ways of making the computer think like a human being, scientists have developed a number of search techniques that can be implemented in order to find a solution to a particular problem. Examples of such search methods are breadth-first search, depth-first search. To make such techniques more efficient, heuristic search methods were developed. The most prominent of these techniques is the best-first search. Process algebra is an algebraic tool for modelling processes in a formal definition. It can be used in a number of different applications, most of which is on concurrency. This paper aims to apply the axioms and elements defined in Process Algebra in coming up with a formalism for the best-first search technique.